THE APPLICATION OF SEMINAR PAPER TECHNIC IN WRITING COURSE IN ENGLISH DEPARTMENT IN FACULTY OF ADAB AND HUMANITY UIN SUNAN AMPEL SURABAYA - Fanani, Abu (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2018)
There three points in this research. These are the proses of the use of paper seminar technic on writing class of English Department, the result of the use of paper seminar technic on writing class of English Department and obstacle of the use of paper seminar technic on writing class of English Department Art and Humanities Faculty, State Islamic University of Sunan Ampel Surabaya. This research method is Classroom Action Research. There are two cycles of this research. The enhancement appeared from the first cycle to the second cycle. It can be seen from the main indicator that shows the improvement. There are some variables that are used but only two variables that are not increase, these are prewriting and drafting.Â  So it can be said that this research is success. While the obstacle of this research are the weakness of students competence of English especially writing skill and the infrastructures that are not support.